Development of a hydrogen cyanide inhalation exposure system and determination of the inhaled median lethal dose in the swine model. (16th April 2018) - Staugler, Jillian M.; Babin, Michael C.; Matthews, M. Claire; Brittain, Matthew K.; Perry, Mark R.
Abstract: Objective: Cyanide is a highly toxic chemical, and acute exposure depletes cells and tissue of oxygen, depressing the respiratory, cardiovascular and neurological systems and potentially leading to death. Cyanide has been used as a weapon since ancient Rome and continues to pose a potential threat today. A well-characterized animal model is necessary for the development of novel methods of rapid detection and treatment. This manuscript describes the development of an inhalation exposure system designed to evaluate the lethality of acute cyanide inhalation in the porcine model. Materials and Methods: A custom designed hydrogen cyanide (HCN) inhalation exposure system provided stable cyanide concentrations to un-anesthetized swine while monitoring respiratory parameters. Real-time respiratory monitoring, cyanide concentration and body weight were used to calculate inhaled doses. Results: The inhalation exposure system generated controlled HCN ranging from 260 to 986 ppm to achieve inhaled doses between 1.78 and 3.97 mg/kg. Based on survival outcomes, the median lethal dose was determined to be 2.21 mg/kg, and the median lethal exposure level was 5893 mg min/m 3 . Discussion: The ability of the HCN inhalation exposure system to deliver target inhaled doses and the determination of the inhaled median lethal dose in swine support the use of the exposure system and animal model for the evaluation of medical countermeasures of acute inhaled HCN toxicity.